Use of microalgae based technology for the removal of antibiotics from wastewater: A review. (January 2020) - Leng, Lijian; Wei, Liang; Xiong, Qin; Xu, Siyu; Li, Wenting; Lv, Sen; Lu, Qian; Wan, Liping; Wen, Zhiyou; Zhou, Wenguang
Abstract: The antibiotic resistance induced by the release of antibiotics to the environment has urged research towards developing effective technologies for antibiotic removal from wastewater. Traditional technologies such as activated sludge processes are not effective for antibiotic removal. Recently, microalgae-based technology has been explored as a potential alternative for the treatment of wastewater containing antibiotics by adsorption, accumulation, biodegradation, photodegradation, and hydrolysis. In this review, the toxicities of antibiotics on microalgae, the mechanisms of antibiotic removal by microalgae, and the integration of microalgae with other technologies such as ultraviolet irradiation (photocatalysis), advanced oxidation, and complementary microorganism degradation for antibiotic removal were discussed. The limitations of current microalgae-based technology and future research needs were also discussed. Graphical abstract: Image 10530169560 Highlights: Antibiotic toxicity and removal performance depend on antibiotic and algal species. Antibiotic removal mechanisms are mainly adsorption, accumulation, and degradation. Combining microalgae with irradiation and oxidation favors antibiotic degradation.